2017
DOI: 10.3389/fpsyg.2017.00552
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Advantages of Bilingual Children in Different Sociolinguistic Contexts

Abstract: Many studies have shown that bilingual children outperform monolinguals on tasks testing executive functioning, but other studies have not revealed any effect of bilingualism. In this study we compared three groups of bilingual children in the Netherlands, aged 6–7 years, with a monolingual control group. We were specifically interested in testing whether the bilingual cognitive advantage is modulated by the sociolinguistic context of language use. All three bilingual groups were exposed to a minority language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
79
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 65 publications
8
79
0
2
Order By: Relevance
“…Although bilingual children' scores on this task were higher than children with typical development, group differences just failed to reach the criterion for statistical significance. These results are also consistent with recent increasing studies of bilingual advantage on working memory tasks [47][48][49][50]. Bilingual superiority in working memory tasks are thought to be arising from the continuous selection and processing of lexical information in two languages.…”
Section: Discussionsupporting
confidence: 91%
“…Although bilingual children' scores on this task were higher than children with typical development, group differences just failed to reach the criterion for statistical significance. These results are also consistent with recent increasing studies of bilingual advantage on working memory tasks [47][48][49][50]. Bilingual superiority in working memory tasks are thought to be arising from the continuous selection and processing of lexical information in two languages.…”
Section: Discussionsupporting
confidence: 91%
“…According to earlier research by Rueda, Posner, Rothbart, and Davis‐Stober (), this area of human development deals with the ability to allocate attention to relevant objects or locations (orienting), maintaining a state of readiness (alertness), and selecting the most goal‐relevant response (executive control). Studies in this theme explored the relationship between bilingualism and selective attention (Blom, Boerma, Bosma, Cornips, & Everaert, ; Chung‐Fat‐Yim, Sorge, & Bialystok, ), attentional processes in low SES bilingual children (Ladas, Carrol, & Vivas, ; Yang & Yang, ), and the role of attentional control in senior adults (Ong, Sewell, Weekes, McKague, & Abutalebi, ). Collectively, the findings supported the bilingual advantage in attentional control tasks and particularly stressed the positive impact of early childhood and adult bilingualism on the attentional system.…”
Section: Resultsmentioning
confidence: 99%
“…There was substantial individual variation on the Flanker task, in particular for the Flanker effect, as revealed by the large SDs. Inspection of the data indicated that this was caused by 18 children who responded relatively fast in the incongruent condition (see also Blom et al, 2017;Rouder & King, 2003). As this pertained to a clear minority of the children in the sample and as the data could not be considered outliers, we decided to include these data in our analyses.…”
Section: Resultsmentioning
confidence: 99%